Pengaruh Citra Perusahaan Bengkel Motor Scooter Jam Jakarta Terhadap Loyalitas Konsumen - M. Rizky; Susi Andrini (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The purpose of this research is to find out how influential corporate image is on customer loyalty (consumer loyalty) for users of Scooter Jam motorcycle repair shops in Joglo, West Jakarta. This study uses Shirley Harrison's theory, which states that a complete fact related to the corporate image. The methodology of this research is explanatory quantitative, which explains the effect of a variable with other variables in testing the hypothesis. Data collection was taken by non-probabilty sampling method using conventional sampling technique. Data collection includes questionnaires, online questionnaires, data analysis, data interpretation, and conclusions. Primary data in the form of a questionnaire on a Likert scale model with a sample of 95 people from a population of 1435 people using the Taro Yamane, Isaac and Michael formula. Statistical analysis and data processing using SPSS. The results of this study indicate that there is a significant influence between Corporate Image at Scooter Jam workshops on its Consumer Loyalty. The benefits of this research include the development of communication science, especially in the field of Public Relations, that corporate image can affect customer loyalty.